La trama hispana de la Primera Conjuración de Catilina - Seguí Marco, Juan José (Gerión. Revista de Historia Antigua, 2001)
Though there are not many references about the political facts that occurred in Hispania along the I century B. C., it must be ramarked the little and careless attention paid to the First Catilinarian Conspiracy of 66 and 64 by the Spanish scholars. Because of the importance that those events have particularly in the Hispanian history and consequently, in the Roman Republican history, the aim of this paper is to revise this question.